Public policy and organizational resilience: Leadership, innovation, and sustainability in the post-pandemic era - Judi, Tjatur Ermitajani; Kurniawan, Daniel (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
In the wake of the global COVID-19 pandemic, the world has witnessed unprecedented challenges and transformations across various sectors. This research embarks on a comprehensive exploration of the multifaceted dynamics that shape organizational readiness for change, innovation capability, and sustainable performance in the post-pandemic era. Drawing upon a systematic literature review, a conceptual model is proposed, elucidating the interconnectedness of organization size, intangibility in assets, leadership styles (with a focus on authentic and servant leadership), financial performance, individual openness to change, implementation of public policy, innovation capability, and sustainable performance. The study underscores the pivotal role of leadership in fostering adaptability and change readiness within organizations, highlighting the significance of authentic and servant leadership styles. It illuminates the value of intangible assets, such as intellectual property and innovation, in driving financial performance and sustainable outcomes. Moreover, the research emphasizes the importance of well-crafted public policies and their impact on risk management, market liquidity, and overall organizational performance. Individual openness to change emerges as a critical factor, influencing the success of policy implementations and innovation initiatives. The study underscores the need for organizations to cultivate cultures of adaptability and resilience to thrive in a rapidly changing landscape. Innovation capability, a cornerstone of competitiveness, is found to be influenced not only by resources but also by leadership styles and intangible assets. Sustainable performance, in this context, extends beyond economic measures to encompass social and environmental responsibility. This research offers a theoretical framework that advances our understanding of the complex interplay among variables shaping organizational resilience and success. While recognizing the limitations inherent in the literature review method, this study provides valuable insights and directions for future empirical research and practical implications for organizations seeking to navigate and prosper in the dynamic post-pandemic world.